PP339 A Budget Impact Model Of The EluviaTM Drug-Eluting Stent from The Australian Public Hospital And National Payer Perspective. (December 2020) - Altaf, Nishath; Ariyaratne, Thathya V.; Peacock, Adrian; Deltetto, Irene; El-Hoss, Jad; Thomas, Shannon; Taylor, Colman; Mwipatayi, Patrice
Abstract : Introduction: Improving long-term outcomes like target lesions revascularizations (TLRs) is a focus for endovascular interventions aimed at treating symptomatic lower-limb peripheral arterial disease (PAD). Eluvia TM, a paclitaxel-eluting drug-eluting stent (DES) was shown to further reduce TLRs when compared with the paclitaxel-coated Zilver® PTX® stent in the IMPERIAL trial, a global, randomized controlled study. This budget-impact evaluation investigated cost-savings from Eluvia-use when compared with Zilver PTX, relying on the 12- to 24-month outcomes from the IMPERIAL trial. Methods: A budget-impact model comparing Eluvia and Zilver PTX was developed from the Australian public healthcare payer, and an individual hospital perspective, with a 5-year time-horizon. Observed trial results were applied to each year's incident population and associated costs, and no extrapolation was conducted. The analysis used publicly available Australian national hospital cost data, population estimates, procedural statistics, epidemiological literature, and data from public hospital audits to verify eligible population for endovascular procedures (EVP) including DES. All costs were captured in Australian dollars (AUD), where AUD 1 = USD 0.69 (June 2020). Results: Assuming 80-percent EVP eligibility, and a DES-use range of 10–28 percent, the 5-year model estimated potential national savings of AUD 4.3–12.1 million (M) [USD 3–8.3M] to the public healthcare payer, driven by reduced TLRs from Eluvia-use compared with Zilver-PTX. The model projected potential national savings of AUD 33.1–92.6M (USD 22.8–63.9M) to individual hospitals through reduced hospital bed days for adverse events (AE). The model forecasted 14, 428–40, 399 treated patients; 1, 499–4, 198 fewer TLRs; and 16, 515–46, 243 fewer hospital days for AE. At a state level, projected hospital savings were: New South Wales AUD 10.9–30.7M [USD 7.5–21.1M]; Victoria AUD 8.4–23.4M [USD 5.8–16.1M]; Queensland AUD 6.5–18.3M [USD 4.5–12.6M]; Western Australia AUD 3.4–9.5M [USD 2.3–6.5M]; South Australia AUD 2.3–6.4M [USD 1.6–4.4M]. Conclusions: Treatment of symptomatic lower-limb PAD with the Eluvia DES could lead to potential savings for the Australian healthcare system, at the national, state, and the local hospital level, based on improved patient outcomes.